Harnessing indigenous knowledge for dairy development: participatory insights from Eastern Rajasthan’s Tribal Belt - Gogoi, Bidyut Pritom; Meena, Brajendra Singh; Sankhala, Gopal; Garai, Sanchita; Sirilakshmi, Yasa; Timba, Mebom; Bhandari, Gunjan; Kumar, Nishant; Mondal, Goutam (Frontiers in Animal Science, 2026)
IntroductionIndigenous Technical Knowledge (ITK) plays a vital role in livestock management, offering low-cost, eco-friendly, and locally adaptable solutions for dairy farming. Despite their significance, these practices are often undocumented, underutilized, and face challenges of declining transmission across generations. Therefore, it is essential to systematically collect and record such indigenous practices and scientifically validate them to evaluate their relevance and applicability under current farming conditions. So, the research study was planned to document and validate the ITKs used by tribal dairy farmers and to identify the constraints faced by them in adoption of ITKs.MethodsThis research employed a mixed sampling methodology and the data collection was done by personal interviews with households. The data were analyzed using various statistical techniques including Mean Perceived Effectiveness Index computation and Garret Ranking technique.ResultsOut of the 44 documented ITKs, 37 were found rational and effective, particularly in broad areas of breeding, feeding (milk production) and health care such as inducing heat, treating repeat breeding, retained placenta, prolapse, diarrhea, bloat, wound healing, and enhancing milk yield. However, major constraints faced by tribal farmers in adoption of ITKs included lack of scientific validation, limited awareness among young farmers, absence of standardized dosage, and inadequate institutional support.DiscussionThe findings confirm that ITKs are socially acceptable, economically viable, and ecologically sustainable for dairy farming. Yet, their wider adoption requires scientific validation, proper documentation, and integration with modern veterinary practices. Addressing the identified constraints through policy support, farmer training, and participatory research can revitalize ITKs for sustainable livestock management.